The study on factors affecting online food delivery services among students in Universiti Malaysia Kelantan - Balqis Mohd Shukri; Kayalvizhi Ramachandran; Lim Kok Soon; Muhammad Suffian Sulaiman (2023)
Online food delivery (OFD) services have recently been a new phenomenon in Malaysia, with various online food applications. Reaching customers and offering them high-quality services are the goals of online food delivery (OFD) providers. Therefore, this study aims to study factors affecting online food delivery services among students in University Malaysia Kelantan (UMK). A quantitative method is used in completing this research. A simple random sampling is used to collect data, and the structured questionnaire was designed to collect data among student at the University Malaysia Kelantan. The statistical package for sciences (SPSS) version 28 was used for data analysis. The result concluded that the independent variable of service quality, price, and delivery time have a significant relationship with online food delivery services in University Malaysia Kelantan. Limitations of this study and recommendations are included in this study to give a better idea for future researchers related to studies involving online food delivery services in University Malaysia Kelantan.